Prediction of Severity and Length of Hospital Stay in Patients with Group 2 Pulmonary Hypertension Based on Serum Potassium Level - GUO Yunting, HOU Xiaomin, BAI Jianying, CHANG Mingyang, ZHAO Xu, SUN Lin, ZHENG Zhifa, SHI Yiwei, QIN Xiaojiang (Zhongguo quanke yixue, 2024)
Background Pulmonary hypertension (PH) is often caused by left heart disease (group 2 PH) , which is difficult to diagnose early and with a high mortality rate. Potassium channel dysfunction is a marker of PH, however, the epidemiological data of the disease and the effect of potassium ions on PH still remain unclear. Objective To investigate the correlation of serum potassium level with myocardial markers, echocardiographic indicators and length of hospital stay in patients with group 2 PH, and evaluate the predictive value of serum potassium levels for the severity of group 2 PH, so as to provide the oretical basis for clinical diagnosis and treatment. Methods The clinical data of 400 adult inpatients diagnosed with group 2 PH in the First Hospital of Shanxi Medical University from January 2020 to December 2021 were retrospectively collected as follows: (1) general data: gender, age, BMI, length of hospital stay, smoking status, smoking index (SI) and drinking history; (2) underlying diseases (diabetes mellitus, hypertension) ; (3) laboratory data: serum potassium level, myocardial markers[procalcitonin, N-terminal pro-brain natriuretic peptide (NT-proBNP) , cardiac troponin I, cardiac troponin T, creatine kinase-MB], echocardiographic indicators (left atrial diameter, right ventricular diameter, right atrial area, left ventricular ejection fraction, shortening fraction, peak tricuspid regurgitation velocity, pulmonary artery systolic pressure) . The patients were divided into <3.5 mmol/L group (n=57) , 3.5-5.5 mmol/L group (n=340) and >5.5 mmol/L group (n=3) according to the serum potassium level. Spearman correlation analysis was used to explore the correlation of serum potassium level with myocardial markers and echocardiographic indicators. Log-rank (Mantel-Cox) test was used to compare the discharge rate of patients with different serum potassium levels. Receiver operating characteristic curve (ROC curve) was plotted to evaluate the predictive value of serum potassium level for the severity of group 2 PH. Results Procalcitonin and NT-proBNP levels of patients in the >5.5 mmol/L group were significantly higher than the <3.5 mmol/L group (P<0.05) . Correlation analysis showed that serum potassium level was positively correlated with NT-proBNP (rs=0.133) , peak tricuspid regurgitation velocity (rs=0.017) and pulmonary artery systolic pressure (PASP) (rs=0.126) (P<0.05) . Serum potassium level was further classified as <3.5 mmol/L, 3.5-3.9 mmol/L, 4.0-4.9 mmol/L, 5.0-5.5 mmol/L, and >5.5 mmol/L to investigate its relationship with length of hospital stay in depth. Log-rank (Mantel-Cox) testresults showed that for group 2 PH patients greater than average hospitalization levels, there was a significant difference in cumulative hospitalization rates among patients with different serum potassium levels (<3.5 mmol/L, 3.5-3.9 mmol/L, 4.0-4.9 mmol/L, 5.0-5.5 mmol/L, >5.5 mmol/L) (P=0.022) . ROC analysis showed that the diagnostic value of serum potassium level for non-mild PH (AUC=0.577, cut-off value=3.91 mmol/L, sensitivity=64.7%, specificity=52.5%) was similar to that of NT-proBNP (AUC=0.585, cut-off value=1 070.69 pg/mL, sensitivity=78.1%, specificity=39.6%) , which can effectively predict the severity of group 2 PH. Conclusion Serum potassium level can predict the severity of group 2 PH and the length of hospital stay. Intervention of serum potassium levels may be one of the new approach to prevent and treat PH.